Pemberdayaan Masyarakat Melalui Pengembangan Ekowisata Berbasis Kearifan Lokal Dalam Mewujudkan Pariwisata Berkelanjutan di Dusun Tuing Desa Mapur Kabupaten Bangka - Sudarmawan, Sudarmawan; Hidayat, Wahyu (SENTRI: Jurnal Riset Ilmiah, 2025)
This study analyzes community empowerment through the development of ecotourism based on local wisdom in Tuing Hamlet. The novelty of this research lies in its integrative examination of social, institutional, and governance dimensions of ecotourism-based empowerment at the hamlet level, emphasizing local wisdom as both a cultural asset and a participatory governance mechanism. The study addresses three research questions: (1) what natural and cultural potentials support ecotourism development in Tuing Hamlet, (2) how local wisdom is mobilized in community empowerment processes, and (3) what structural challenges constrain empowerment outcomes. A qualitative approach was employed using observation, in-depth interviews, and document analysis. Data were analyzed through thematic analysis, involving data reduction, coding, categorization, and interpretation to identify key patterns of empowerment and existing constraints. The findings indicate that Tuing Hamlet possesses significant potential for ecotourism development, supported by the establishment of the Kelompok Tani Hutan (KTH) Pulau Punggur as a formal management institution and active participation of community groups, including youth, traditional leaders, and women’s organizations (PKK), in decision-making processes. This participation has fostered an emerging sense of community agency. However, empowerment remains at an early stage due to several challenges: limited access to financial resources caused by dependence on a single investor and the absence of government support, restricted access to knowledge and training, weak and non-transparent governance resulting from the lack of binding technical regulations, and the absence of direct economic benefits as ecotourism activities are not yet fully operational. These findings imply that sustainable ecotourism-based community empowerment requires structural strengthening through diversified funding sources, continuous capacity building, inclusive partnerships, and transparent internal governance mechanisms.